Factors associated with hospital admission in patients reaching the emergency department with COPD exacerbation - García-Sanz Maria; Pol-Balado Carlos; Abellás Concepción; Cánive-Gómez Juan; Antón-Sanmartin Diana; González-Barcala Francisco J (Multidisciplinary Respiratory Medicine, 2012)
Abstract Background The aim of this study was to determine the frequency of COPD exacerbations in our Emergency Department, as well as the hospitalization-related factors. Methods Prospective observational study conducted in the Emergency Department of Salnés County Hospital among patients admitted for COPD exacerbation. Admission predictors were determined by multivariate analysis. Results There were 409 exacerbations in 239 patients (79% male, mean age 75). 57% of exacerbations required hospitalization. Hospitalization-related factors were impaired oxygenation (p < 0.001), presence of neutrophilia (p < 0.01) and prescription of antibiotics in the Emergency Department (p < 0.05). Conclusions COPD exacerbation accounts for over 1% of all visits to our Emergency Department. 57% of them required hospitalization. Impaired oxygenation, greater neutrophilia and prescription of antibiotics in the Emergency Department were associated with greater probability of admission.